Zebrafish as a pharmacological tool: the how, why and when - Goldsmith, Paul (Current opinion in pharmacology, 2004)
Zebrafish combine the relevance of a vertebrate with the scalability of an invertebrate. They can live in 96-well plate format and readily absorb chemicals from the water. These features have stimulated the use of zebrafish by medical researchers to model human disease and then assess the action of compounds in a whole organism. Examples of the power of this system have been illustrated with the cloning of zebrafish human ether-a-go-go-related gene (HERG), which shows near 100% homology in key domains, and the associated ability to identify drugs that prolong the QT interval both rapidly and with tiny amounts (micrograms) of compound.